ナンキョク ミズホ カンソク キョテン ニ オケル ジフブキ リョウ ノ ソクテイ - 井上, 雅之; イノウエ, マサユキ; 藤野, 和夫; フジノ, カズオ; Inoue, Masayuki; Fujino, Kazuo (国立極地研究所, 1977)
P(論文) 第15次南極地域観測隊に参加して,みずほ観測拠点において地吹雪量測定を行った,引出し箱型地吹雪計を改良した結果,サイクロン型地吹雪計とほぼ同じ捕捉率(⫩0.55)をもつことがわかったので,引出し箱型地吹雪計を用いて雪面上1mまでの高さの各層における地吹雪量を風速分布とともに詳細に解析した.得られた地吹雪密度分布から,地吹雪は雪面上約25cmの高さまではサルティションの卓越している層であり,それより上部では地吹雪粒子が渦拡散により浮遊している層であると考えた.地吹雪輸送量は雪面上10mの高さでの風速値と良い相関があった.この関係を用いると,みずほ観測拠点での全地吹雪輸送量は,約0.64×10^6 ton・km^<-1>・year^<-1>と見積もることができた. Measurements were carried out simultaneously of drifting snow and wind speed over the surface from 1974 to 1975 at Mizuho Camp using an improved drawer-type drift collector which had a collection efficiency of about 0.55. From the obtained profile of spatial distribution of drift mass flux, it is considered that a layer from the surface to a height of about 25 cm is the one in which the saltation of snow particles prevails and a layer on top of it is the one in which snow particles are suspended by turbulent diffusion. A significant correlation was found between the total drift transport and the wind speed at the height of 10 m above the surface. The total drift transport at Mizuho Camp evaluated from this correlation was about 0.64×10^6 ton・km^<-1>・year^<-1>. departmental bulletin paper